Testing a Hump-Shaped Pattern with Increasing Elevation for Ant Species Richness in Daliang Mountain, Sichuan, China - Shi-Jia You; Zheng-Hui Xu; Xin-Min Zhang (Diversity)
Ants have long been regarded as ubiquitous insects that are indicators of environmental change and ecosystems. Understanding the patterns of ant species richness along elevational gradients is crucial for elucidating their ecological functions within ecosystems. However, there is currently no comprehensive consensus on the pattern. In this study, we explored the pattern of ant species richness along an elevational gradient in the Mt. Daliang region (Sichuan, China), a biodiversity conservation hotspot in China. The ant species richness was investigated using 115 plots 50 × 50 m in size, distributed across 12 elevation bands of 250 m interval between 750 to 3500 m a.s.l. We identified 157 ant species from 51 genera and seven subfamilies. Myrmicinae was the most diverse subfamily, consisting of 20 genera and 84 species, followed by Formicinae, Dolichoderinae, Ponerinae, Dorylinae, Amblyoponinae, and Proceratiinae. We found a unimodal distribution pattern of ant species richness along the elevational gradient, with the highest ant species richness occurring at mid-elevations. This hump-shaped pattern of ant species richness was presented alongside the temperature variation. Furthermore, our results indicated that ground-foraging ant species were the most abundant in this region and that ants prefer to nest in the soil. Our findings highlight the importance of elevation in influencing ant species richness in Daliang Mountain, Sichuan, China, and provide novel insights into the potential drivers of elevational gradients in ant species communities.